Comparativo microbiológico de queijos artesanais produzidos no município de Montes Claros - MG nos períodos de chuva e seca - Maria Fernanda Santos Calzavara (2023)
Widely produced in the state of Minas Gerais and consumed throughout Brazil, artisanal cheeses are characterized, for the most part, by production in small rural properties, being an important source of family income. Sanitary control is often flawed in the production of artisanal cheeses, so as not to guarantee a good microbiological quality of the final product, which could endanger the health of the consumer. Problems such as the production environment, the seasonality of the seasons and the handler's lack of hygiene are the main points that must be observed in order to avoid microbiological contamination, all of which are linked to Good Manufacturing Practices (GMP) and Good Milking Practices. Thus, the present work aimed to carry out a microbiological analysis regarding the presence of Escherichia coli, Staphylococcus aureus, coliforms, Listeria monocytogenes and Salmonella spp. in 80 samples from producers in the municipality of Montes Claros/MG, 40 from the dry season and 40 from the rainy season. The results indicated contamination of all samples at values higher than the legislation, except for Listeria monocytogenes and Salmonella spp. The need for greater supervision by the competent bodies is evident, as well as training for employees and improvements to production sites.